XX/XY sex chromosome system and chromosome markers in the snake eel Ophisurus serpens (Anguilliformes: Ophichtidae). Issue 2 (7th February 2018) - Salvadori, Susanna; Deiana, Anna Maria; Deidda, Federica; Lobina, Cinzia; Mulas, Antonello; Coluccia, Elisabetta
ABSTRACT: We report evidence of an XX/XY sex chromosome system in the snake eel Ophisurus serpens (Anguilliformes: Ophichthidae). We characterized the male and female karyotypes by C-, replication- and Hae III-bandings. The 45S and 5S ribosomal gene families were located using dual fluorescence in situ hybridization, which showed that the 5S rDNA sites were present on the X chromosome, beside an autosome pair. FISH with a telomeric peptide nucleic acid probe enabled recognition of Interstitial Telomeric Sequences (ITSs), likely remnants of chromosomal rearrangements, in five chromosome pairs, including the rDNA-bearing ones. Possible mechanisms of the origin of sex chromosomes in this species are discussed, considering the presence of a sex-linked marker and ITSs.